(untitled) (Research, Society and Development, 2021)
In this work, we present studies that used quantum-chemical calculation as a tool for predicting behaviors in chemistry and molecular physics, which provided highly accurate and quantitative data on molecular systems. We start by reviewing the theory of electronic structure based on the wave function, emphasizing the N-electronic hierarchy of the pair-cluster theory and the one-electron hierarchy of sets of consistent bases of correlation. Later, we show studies carried out in different areas of chemistry in which quantum data were used to study the behavior of compounds in different areas of modern chemistry. A great advantage of the use of computational quantum chemistry is the possibility of studying mechanistics that are not experimentally feasible to be performed, but the data provided by it guarantee great reliability of the presented data. Computational chemistry has become a very useful tool in modern chemistry.